Effectiveness of a program based on social theory in the achievement of curriculum and textbook material for students of basic education faculties (Journal of the College of Basic Education, 2022)
This research aims to (The effectiveness of a program based on social theory in the achievement of curriculum and textbook subjects among students of the colleges of basic education). The researcher adopted an experimental design with partial control, which is the design of the control group with a post-test. So the researcher formulated the following hypothesis:There is no statistically significant difference at the level of significance (05, 0) between the average scores of the experimental group students who study the curriculum and textbook material in the program based on social theory and the an average scores of the control group students who study the same subject in the traditional program in the achievement test. The researcher intentionally choses the College of Basic Education / University of Diyala as a sample for her research, which includes four divisions for students of the fourth stage / Department of Arabic Language. By simple random drawing, Division (C) became the experimental group whose students will study the curriculum and the textbook according to the program based on social theory. The number of its students is (40) male and female. Division (D) represents the control group whose students will study the same subject according to the regular program and the number of It was requested by (42) male and female students. Thus the number of the research sample became (82) male and female students. After applying the experiment, the researcher excluded (6) students from the experimental group, (9) students from the control group, due to the exceptional circumstance (the Corona pandemic) and was absent Students refrained from attending electronic lectures, so that the results would be more accurate, and thus the number of the research sample became (68) male and female students.The researcher was statistically rewarded between the students of the two research groups in the variables (intelligence test, prior knowledge test, self-academic motivation scale). As for the research tool, the researcher prepared an achievement test that includes (45) items distributed among objectivity items (40) items, and five essay items. And the Pearson correlation coefficient, the Spearman-Brown correction equation, and the Eta-squared, the results of the research resulted in a statistically significant difference between the average scores of the students of the two research groups in the achievement test at a significance level (0.05) and a degree of freedom (66) in favor of the experimental group, and thus we reject the null hypothesis And to complement the level of statistical significance, the researcher applied (ETA squared) to measure the size of the impact of the program, and the program was effective, that is, the proposed program had a positive impact on students’ achievement. Confirming the validity of previous studies regarding the effectiveness of social theory in achievement.